2014
DOI: 10.1098/rspa.2014.0576
|View full text |Cite
|
Sign up to set email alerts
|

Study of dynamic underwater implosion mechanics using digital image correlation

Abstract: The physical processes associated with the implosion of cylindrical tubes in a hydrostatic underwater environment were investigated using high-speed three-dimensional digital image correlation (3D DIC). This study emphasizes visualization and understanding of the real-time deformation of the implodable volume and the associated fluid–structure interaction phenomena. Aluminium 6061-T6 cylindrical tubes were used as the implodable volumes. Dynamic tourmaline pressure transducers were placed at selected locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Turner and Ambrico identified the key features of a typical mode-2 implosion process by correlating the important signatures of the pressure pulse with the structural deformation [3]. Farhat et al extended this work by comparing both mode-4 and mode-2 implosion, and showed that the higher mode of collapse generates a higher pressure peak but of smaller duration compared to that obtained in a lower mode collapse [13], Recently, Gupta et al uti lized a high speed digital image correlation technique to capture the real-time deformation of the implodable volumes, and showed that the time period and impulse of the positive pressure wave directly correlates to the time taken for the collapse to propagate along the length of the implodable volume [15].…”
Section: Introductionmentioning
confidence: 98%
“…Turner and Ambrico identified the key features of a typical mode-2 implosion process by correlating the important signatures of the pressure pulse with the structural deformation [3]. Farhat et al extended this work by comparing both mode-4 and mode-2 implosion, and showed that the higher mode of collapse generates a higher pressure peak but of smaller duration compared to that obtained in a lower mode collapse [13], Recently, Gupta et al uti lized a high speed digital image correlation technique to capture the real-time deformation of the implodable volumes, and showed that the time period and impulse of the positive pressure wave directly correlates to the time taken for the collapse to propagate along the length of the implodable volume [15].…”
Section: Introductionmentioning
confidence: 98%
“…This implosion process is shown to be highly violent in nature with resulting high velocity water motion and strong shock waves [6]. There have been several investigations reported by researchers in naval and marine communities on the mechanics and fluid-structure interaction during an implosion process [2,[7][8][9][10][11][12][13][14][15][16][17][18][19]. Although the evolution of implosion pressure waves and its relation to structure geometry has been widely studied, there is a little information on the interaction of these pressure waves with the adjacent structures and on the potential of damage/sympathetic implosion.…”
Section: Introductionmentioning
confidence: 99%
“…A coarse high contrast random pattern (bullet points of diameter approximately equal to mm) has been painted on a mock target plate such that the transition between black and white area corresponds to approximately four pixels [5]. After calibration, correlation was successful in the ROI 2 . Figure 2 shows the mock target in reference and rotated positions and its shape reconstruction by stereo-correlation.…”
Section: Preliminary Studymentioning
confidence: 99%
“…Deformations are often measured by strain gages [1] but particular attention has been paid recently to 3D digital image correlation (DIC) for HVI or blast [2]- [4] when region of interest (ROI) remains properly visible during test. The main challenge is to find a compromise between measurement accuracy and size of the ROI because of the lower resolution of high speed cameras.…”
Section: Introductionmentioning
confidence: 99%